Management of Chronic Ginggivostomatitis In Local Cats With A History of Recovery From Feline Calici Virus - Mar'atul Halim Nafi'ah; Putu Ayu Sisyawati Putriningsih; I Gusti Made Krisna Erawan (Journal of Applied Veterinary Science And Technology, 2025)
Background: Feline chronic gingivostomatitis (FCGS) is a chronic oral inflammatory condition that often affects cats. The cause of this condition is reported to be closely related to the immune system in its pathogenesis and infectious agents such as feline calici virus (FCV) along with bacterial infections. Purpose:  To inform how to diagnose, and provides alternative treatment for patients with FCGS problem. Case: A cat presented for examination due to complaints of mouth scratching, such as food debris being stuck and the cat being very sensitive to touch at the mouth. The case cat was diagnosed with feline calici virus and eventually recovered. Before the case cat's recovery from FCV, the cat was very sensitive to touching its mouth. The case cat appeared generally healthy and active, but there was inflammation throughout the gums, also there was a foul odor. The palatoglossal area looked reddish, swollen, and there were ulcerative lesions. Supporting examinations performed were routine blood tests, oral swab cytology, and confirmation of Ag FCV and feline herpes virus (FHV-1) test kits due to suspicion of recurrence and other viral infections. Cytological swab examination showed neutrophils and blue coccus-shaped gram-positive bacteria, while the results of the Ag FCV and FHV test kits showed negative results. Based on all examination, the case animal was diagnosed with feline chronic gingivostomatitis (FCGS). Case Management:  The therapy given included the administration of amoxicillin-clavulanate acid syrup antibiotics, methylprednisolone as anti-inflammatories, and multivitamin as supportive therapy. Conclusion: Evaluation of the treatment was carried out periodically and on day 21 the lesions found on the palatoglossal and the inflammation had disappeared.